Impact of Liquidity and Risk on Dividend Policy: A Mediating Role of Investment (The International Research Journal of Management Science, 2024)
Purpose: The aim of this study is to analyze the influence of liquidity and risk on dividend policy in the nepalese banking sector, with a specific focus on examining the mediating role of investment in the relationship between liquidity and risk and the dividend policy.Methods/Design: The study uses a questionnaire survey, gathering 356 responses from bank managers in Nepal representing various banking categories. It adopts a descriptive and correlational research design, incorporating regression analysis and structural equation modeling (SEM) using AMOS to achieve its objectives.Findings: The results indicate that investment significantly mediates the relationship between liquidity, risk, and dividend policy. Specifically, firms with higher liquidity and greater risk are more likely to invest in profitable projects, which are expected to lead to increased profit distribution within the banking sector in the future.Implications/Limitations: These insights are valuable for both financial managers and policymakers in the Nepalese banking sector. However, the study is limited to the banking sector in Nepal and may not generalize to banks in other regions or financial systems.Originality: This study provides a unique perspective on the interaction between company risk and dividend policy in Nepalese banks, filling a gap in the literature on risk management and shareholder value within the context of emerging economies.